Social-ecological system approaches for water resources management. Issue 2 (17th February 2021) - Gain, Animesh K.; Hossain, Sarwar; Benson, David; Di Baldassarre, Giuliano; Giupponi, Carlo; Huq, Nazmul
ABSTRACT: In the era of the Anthropocene, understanding the dynamic interactions between humans and water is crucial for supporting both human well-being and the sustainable management of resources. The current water management challenges are inherently unpredictable and difficult to control. Social-ecological systems (SESs) approaches explicitly recognize the connections and feedbacks between human and natural systems. For addressing the complex challenges of the Anthropocene, consideration of SES attributes such as causality (or interdependence), feedback, non-linearity, heterogeneity, and cross-scale dynamics is important. In addition, innovative qualitative and quantitative methods such as Bayesian networks, agent-based modelling, system dynamics, network analysis, multicriteria analysis, integrated assessment and role-play games have recently been used in SES research. The overall goal of this review is to gauge the extent to which SES attributes and methods are considered within the current interdisciplinary water paradigm. The paper therefore develops the normative theoretical characteristics of SES in terms of its key attributes (i.e. causality, feedback, heterogeneity, nonlinearity, and cross-scale dynamics) incorporated in the water paradigm approaches. The paper then compares the methods applied in the interdisciplinary water paradigm and examines how they can complement each other. Finally, the paper reflects back on the usefulness of SES attributes and methods for assessing the interdisciplinary water paradigm and makes recommendations for future research.